1998
DOI: 10.1177/106591299805100307
|View full text |Cite
|
Sign up to set email alerts
|

Attack Politics in Presidential Nomination Campaigns: An Examination of the Frequency and Determinants of Intermediated Negative Messages Against Opponents

Abstract: This article explores the negative campaign messages made by presidential nomination candidates on their opponents. Using a compilation of national and state media accounts of candidate attack activity from the 1992 Democratic nomination race, we seek to answer the questions --are the intermediated attacks made by presidential nomination candidates random events or are they predictable consequences of measurable variables ? Moreover, when candidates attack, who is their likely target? We find that intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
56
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 23 publications
1
56
3
Order By: Relevance
“…A study of the 1992 Democratic nomination found that races that get more media attention are more likely to have negativity (Haynes and Rhine 1998), whereas primary campaigns from 1998 with more media attention were no more likely to be negative (Peterson and Djupe 2005). It is not clear how these studies of media attention in the primaries would apply to general elections.…”
Section: Determinants Of Negativitymentioning
confidence: 97%
“…A study of the 1992 Democratic nomination found that races that get more media attention are more likely to have negativity (Haynes and Rhine 1998), whereas primary campaigns from 1998 with more media attention were no more likely to be negative (Peterson and Djupe 2005). It is not clear how these studies of media attention in the primaries would apply to general elections.…”
Section: Determinants Of Negativitymentioning
confidence: 97%
“…2 We attempt to examine all tweets in which one of the 17 Republican presidential hopefuls in 2016 mentions another candidate, investigating the degree to which candidates' relative standing and stage of the campaign predict propensity to attack one another on Twitter. We anticipate increasing negativity among all candidates as primaries and caucuses approach (Damore 2002 ;Haynes and Rhine 1998 ;Lau and Pomper 2001 ), either due to the narrowing of the fi eld (Haynes and Rhine 1998 ;Hale, Fox, and Farmer 1996 ;Lau and Pomper 2001 ;Druckman, Kifer, and Parkin 2010 ;Kahn and Kenney 2002) or because opportunities grow scarce as elections approach (Peterson and Djupe 2005 ;Haynes and Rhine 1998 ;Damore 2002 ). Alternatively, a fi eld of many plausible contenders may promote negative campaigning early on as candidates struggle to separate from the pack (Peterson and Djupe 2005 ;Djupe and Peterson 2002 ).…”
mentioning
confidence: 99%
“…Furthermore, we expect candidates to launch attacks primarily "upward" at those with better prospects, having less incentive to attack those deemed less of a threat (Skaperdas and Grofman 1995 ;Thielmann and Wilhite 1998 ;Lau and Pomper 2001 ;Damore 2002 ;Druckman, Kifer, and Parkin 2010 ;Haynes and Rhine 1998 ). One open question is whether candidates will focus their attacks upon their leading competitor (Skaperdas and Grofman 1995 ) or go negative against multiple competitors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The studies in this literature most directly related to the current paper measure the determinants of negative campaigning. These papers include Damore (2002), Haynes and Rhine (1998), Kahn (1993), Lau and Pomper (2001), Proctor, Peterson and Djupe (2005), and Schenck-Hamlin and Haase (1994), among others. Relying on various types data on campaign negativism, the studies focus on potential causal factors such as the support difference between candidates, presence of an incumbent, party affiliation, gender, and proximity to the election date.…”
Section: Introductionmentioning
confidence: 99%